Religious Education beyond Congregational Settings - Turpin, Katherine (Religions, 2018)
Religious educational literature in the United States often presumes the congregation as the primary context for the work of faith formation. Given the reduction of institutional affiliation and participation in Christian congregations, this assumption makes approaches to religious education requiring an identity-bearing community of affiliation less relevant. Several emerging models of religious education eschew the community provided by formal religious institutions for more provisional, radically contextualized communal approaches to religious education. These approaches spark a different and important imagination for religious education beyond congregations, embedded in provisional communities of solidarity and engagement.